Forecasting Indicators of Business Development in Uzbekistan - Akbarov Shokhabbos Khakimjon ugli (Study Program Ekonomi Syari'ah, Sekolah Tinggi Agama Islam Muhammadiyah Tulungagung, 2022)
The article is devoted to econometric modelling and forecasting of business development using correlation and regression analysis. Also, a model for the development of GDP business is given, taking into account the indicators of the share of business in the number of employees in the volume of agricultural production, exports of the Republic of Uzbekistan and the forecast value of the share of business in GDP by 2017-2021.